A comparative study to Evaluate Shear Bond Strength of Metal and Resin Brackets by using two types of adhesives. - حسن حازم; عدسو جانا (Latakia University Journal -Medical Sciences Series, 2021)
Objective: The aim of this study was to evaluate the difference of shear bond strength between metal and resin brackets by using composite and compomer used in bonding orthodontic brackets and to determine how these forces are close to clinically acceptable values. Material and Methods: The research sample consisted of 200 intact upper human premolars teeth freshly extracted for orthodontic purposes, randomly divided into four equal groups. Metal brackets were bonded with a light-cured composite in the first group and with a light-cured compomer in the second group. Resin brackets were bonded with composite in the third group and with compomer in the fourth group. The specimen teeth were subjected to thermocycling of 200 cycles and then the shear bond strength was tested with a universal testing machine. Results: The results showed that mean shear bond strength of metal brackets bonded with composite was significantly different from that of the metal brackets bonded with compomer in group (2), the resin brackets bonded with composite in croup (3) and the resin brackets bonded with compomer in group (4) at the significance level of 0.01.